Oils, paintings and chemistry - Maria Eduarda Machado de Araújo (Conservar Património, 2005)
In oil paintings artists use oils to apply pigments. These oils firstly are liquid and then solidify in a thin film. Many chemical reactions are involved in drying and also in the aging of these oils. Drying is a continuous process that begins with the oxidation of insaturated fatty acids from triglycerides to originate peroxides. These compounds suffer a cascade of reactions that lead to cross linking bonds between fatty acids residues, transforming the oil in a solid film. Identification of the film oil is possible using the palmitic/stearic ratio (P/S) by chromatographic (GC) and/or spectroscopic techniques. Sterol composition, phytosterols or cholesterol, determined by GC-MS or FTIR techniques, allows investigators to distinguish between oil painting and a temper one that used egg as the binding medium.